The Clinical History and Basic Science Origins of Transcutaneous Osseointegration for Amputees. (18th March 2022) - Hoellwarth, Jason Shih; Tetsworth, Kevin; Akhtar, Muhammad Adeel; Al Muderis, Munjed
Abstract : Transcutaneous osseointegration for amputees (TOFA) refers to an intramedullary metal endoprosthesis which passes transcutaneously to connect with a limb exoprosthesis. The first recognizably modern experiments and attempts occurred in the 1940s. Multiple researchers using a plethora of materials and techniques over the following 50 years identified principles and obstacles which informed the first long-term successful surgery in 1990. Unfortunately, the current mainstream TOFA literature presents almost exclusively subsequent developments, generally omitting prior research, leading to some historical mistakes being repeated. Given the increasing interest and surgical volume of TOFA, this literature review was performed to delineate TOFA's basic science and surgical origins and to integrate these early efforts within the contemporary understanding. Studying this research could protect and benefit future patients, surgeons, and implant developers as TOFA is entering a phase of increased attention and innovation. The aim of this article is to provide a focused reference of foundational research, much of which is difficult to identify and retrieve, for clinicians and researchers.